Optimal data allocation and fairness for online games. (1st January 2014) - Kohana, Masaki; Okamoto, Shusuke; Ikegami, Atsuko
In our previous work, we proposed a load distribution technique and a dynamic data reallocation method for web-based Multiplayer Online Role-Playing Game (MORPG) systems. Our proposed approach reduced the average server latency for game players. However, latency values varied widely resulting in some game players gaining an advantage over others. In this paper, we deal with data allocation and consider latency fairness in the form of a combinational optimisation problem. We develop an optimisation model in which the objective function minimises the differences in latency values and we solve instances from this model using an exact algorithm. Our model improved latency fairness and more stable server loads than the previous data reallocation method. Furthermore, it provides more stable gameplay using ten web servers instead of five.